PENGEMBANGAN APLIKASI SURVEI ANDROID TERENKRIPSI DENGAN VALIDASI LOKASI UNTUK ASESMEN PSIKOLOGIS: DEVELOPMENT OF AN ENCRYPTED ANDROID SURVEY APPLICATION WITH LOCATION VALIDATION FOR PSYCHOLOGICAL ASSESSMENT - Nanda Nan Arif H; Muhammad Fikry; Zara Yunizar (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2025)
Digital data collection in psychological contexts requires systems that are not only efficient but also secure and context-aware. This study develops an Android-based survey application with layered security by integrating GPS-based location validation and AES-128 encryption. The system restricts access to predefined geographic areas, and all user data is encrypted exclusively on the server side (Laravel backend) to ensure confidentiality and integrity. Indoor testing of location validation showed high accuracy with a 50-meter tolerance and an average response time of 50 ms. Encryption was performed in 40–110 ms for data up to 19.7 KB. Communication between the mobile app and the server uses a REST API secured with HTTPS. The application was developed using the Waterfall model, which fits the structured and pre-defined system requirements. This study’s novelty lies in combining real-time location validation and server-side encryption in a single system—an approach often handled separately in prior research. Black-box testing confirmed that the system performs securely and reliably without burdening the device. This solution is suitable for mobile-based psychological assessments in controlled environments such as schools and is adaptable for other services requiring simultaneous data protection and location verification.